2012
DOI: 10.1111/hex.12026
|View full text |Cite
|
Sign up to set email alerts
|

Why do hospitalized older adults take risks that may lead to falls?

Abstract: Background The behaviour of hospitalized older adults can contribute to falls, a common adverse event during and after hospitalization.Objective To understand why older adults take risks that may lead to falls in the hospital setting and in the transition period following discharge home. Design Qualitative research.Setting and participants Hospital patients from inpatient medical and rehabilitation wards (n = 16), their informal caregivers (n = 8), and health professionals (n = 33) recruited from Southern Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 26 publications
5
85
0
9
Order By: Relevance
“…Prior studies have demonstrated an increased risk of falls in hospitalized stroke patients 21,25,34,43,48 and in individuals admitted to Neuroscience and Neurosurgery services. 21,25,34,36,40,43,48 The high proportion of UTIs probably reflects intraoperative use of urinary catheters secondary to procedural length and inherent need for osmotic diuresis. A recent study by Titsworth et al suggests that comprehensive UTI prevention efforts along with continuous quality improvement programs can significantly reduce the duration of urinary catheterization and the rate of catheterassociated UTIs in a neurological ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated an increased risk of falls in hospitalized stroke patients 21,25,34,43,48 and in individuals admitted to Neuroscience and Neurosurgery services. 21,25,34,36,40,43,48 The high proportion of UTIs probably reflects intraoperative use of urinary catheters secondary to procedural length and inherent need for osmotic diuresis. A recent study by Titsworth et al suggests that comprehensive UTI prevention efforts along with continuous quality improvement programs can significantly reduce the duration of urinary catheterization and the rate of catheterassociated UTIs in a neurological ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, including an analysis of a large US national data set of over 165 000 falls, have demonstrated that over 85% of falls are not witnessed;2 therefore, patients need to be aware of how to initiate activities safely on the ward, when not in the immediate presence of assisting staff. Other researchers have also stated that if hospital falls prevention is to be effective, it is vital that patients are considered part of the team,25 26 33 34 and that the falls prevention plan should be communicated directly to the patient and their family 2734 The staff perspectives concurred with the educators' perspectives about how the programme worked.…”
Section: Discussionmentioning
confidence: 97%
“…This perspective was also taken by the patients and the educators, suggesting that the education facilitated useful communication between staff and patient and was critical to patients engaging in safe behaviours such as ringing the bell 2223 Other qualitative studies have also identified that patients may feel reluctant to ring the bell to seek help, and that staff think that it is important to emphasise to patients that they should feel confident to ring the bell for assistance 2528 34 One staff member felt that nurses' instructions were sufficient and that the patient education programme was not required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The situations pointed out in the literature in which patients need to request personal assistance are those activities in which, due to the reduction of their abilities, they are no longer able to perform alone, such as getting out of bed and/or going to the bathroom (12,26) . Conceptual definition: the patient describes his or her knowledge about when to ask for help to perform activities that is not able to perform alone due to physical limitation.…”
Section: Indicator (182808) When To Ask For Personal Assistancementioning
confidence: 99%